The Principle of Da'wah at-Tafhim la Talqin in the Da'wah of Arrazy Hasyim from the Perspective of Jum'ah Amin 'Abdul Aziz - Marya Ulfa; Lilis Muchlisoh; Achmad Zaki Ghufron; Maftukhatul Azizah; Moh. Ali Aziz; Alfiansyah Husin (Busyro: Jurnal Dakwah dan Komunikasi Islam, 2025)
This study analyzes the principle of da'wah at-Tafhim la Talqin in Arrazy Hasyim's da'wah on Youtube entitled "How Noble the Prophet SAW is!" This principle prioritizes on providing understanding (at-Tafhim), invitation, and guidance rather than lecturing (talqin), mocking, and judging in delivering da'wah messages that leave an impression on da'wah partners. The analysis method in this study is Miles and Huberman's content analysis by reducing data, then the data is presented according to categories, then conclusions are drawn. Aiming to find out the constructive meaning of the principle of at-Tafhim la Talqin in Arrazy Hasyim's da'wah, the results of the study show that the at-Tafhim approach in Arrazy Hasyim's videos is able to build understanding and awareness of da'wah partners in understanding and carrying out religious messages.  It shows that this approach becomes an effort to convey communicative and educational messages to all groups of societies.